Evolution of fault-related seismic behaviour at Nickel Rim South Mine - Simser, B; Yadav, P; Butler, T (Deep Mining 2024: Proceedings of the 10th International Conference on Deep and High Stress Mining, 2024)
The majority of the larger seismic events (above MW2.0) occurring at Glencore’s Nickel Rim South Mine can be attributed to fault slip. In the mine’s history, 21 larger seismic events have been recorded, and 20 of them locate in proximity to known geological structures. The damage from these events is highly variable, and the intensity and extent of the observed damage can be attributed to the energy radiation pattern, local stress conditions and incapability of installed ground support. This paper describes general seismic observations, emphasising the larger-magnitude fault-slip events. These seismic events have a significant areal extent, which in turn guides the mine’s multi-tiered risk mitigation strategy that limits exposure and utilises dynamic ground support as a last line of defence. The dense microseismic array deployed at the mine has been a key tool for understanding which faults can be classified as ‘seismically active’ and how that activity progresses over time and mining. The smaller-magnitude seismic events help identify linear/planar trends away from stoping areas. In some cases, evident fault trends extending well below the mining horizons or deep into the footwall or hanging wall were observed well before the large seismic events associated with these structures occurred. Some examples of these trends are presented, along with discussions on how the precursory trends can be used to support and inform the mining strategy. Although the mine’s seismic risk management strategy has been very effective, there are still rockburst occurrences with varying degrees of warning and overall complex behaviour. In the cases described, no injuries occurred and the overall safety record of the mine has been excellent. This paper provides insights from an operational perspective. Further research is required to improve fault-slip forecasting and to develop riskmitigation strategies. Some thoughts on potential areas of interest and suggested focus are given in the conclusion section.
Keywords: fault-slip seismicity; rockburst damage; seismic monitoring; seismic risk management